Anti-RANKL treatment improves screw fixation in cancellous bone in rats. Issue 6 (June 2015) - Bernhardsson, Magnus; Sandberg, Olof; Aspenberg, Per
Abstract: Bisphosphonates improve implant fixation in randomised clinical trials of knee prostheses, hip prostheses and dental implants. However, a limited amount of bone resorption is required for bisphosphonates to exert an effect. Anti-RANKL treatment does not have this limitation, and we therefore tested whether if they might be more effective for improvement of implant fixation. This is of interest, as anti-RANKL treatment with denosumab is now in common clinical use. Male SD rats received a stain-less steel screw in the right proximal tibia and a drill hole in the left ( n  = 42). They were randomised to subcutaneous injections of either alendronate (20 μg/kg/day), alendronate (200 μg/kg/day), osteoprotegerin with an Fc tag (OPG-Fc; 8 mg/kg, twice weekly), or saline control. After 4 weeks, the fixation of the steel screw was measured by pull-out test. The tibia with the drill hole was evaluated with μCT. OPG-Fc increased the pull-out force compared to saline controls by 153% ( p  < 0.001). There was no significant difference between OPG-Fc and the alendronate groups. OPG-Fc increased the bone density (BV/TV) in the previous drill hole compared to controls 7-fold ( p  < 0.001). This increase was higher than with any alendronate dose ( p  < 0.001). OPG-Fc increased the bone density of the L5 vertebral body, but there was no significant difference between OPG-Fc and alendronate. Our results suggest that screw fixation in cancellous bone can be dramatically improved by an anti-RANKL agent. The effect was comparable to very high bisphosphonate doses. Screw insertion in cancellous bone elicits a metaphyseal fracture healing response, and our findings might be relevant not only for implant fixation, but also for fracture healing in cancellous bone.